ANALYSIS AND DESIGN OF THE BPK RI LIBRARY INFORMATION SYSTEM REPRESENTATIVE OF CENTRAL KALIMANTAN PROVINCE ANDROID BASED - Candra, Candra; Prabowo, Agung; Suratno, Suratno (Jurnal Sains Komputer dan Teknologi Informasi, 2023)
Library staff record books and it takes a relatively long time and is less accurate. In addition, visitors have not been able to get the information provided by the library directly, be it announcement information, news about the library, agenda of events carried out in the library. Library's web can only be accessed by library employees. Using the PIECES analysis method, and tools using UML (Unified Modeling Language), as well as interface design using Figma and draw,io are used to describe data flow diagrams. Android which can be used by the office as a reference if you want to develop or implement it into a program. The results of this research has been presented to the office, where they have also provided feedback through filling out questionnaires. Overall, based on the results of the questionnaire analysis, it can be concluded that the design of an Android-based library obtains an interpretation value of 96% so that it can be concluded that the design has followed the needs of the user's system.